Genetic Risk Score Associations With Cardiovascular Disease and Mortality in the Diabetes Heart Study - Cox, Amanda J. (American Diabetes Association, 2014)
OBJECTIVE: Given the high rates of cardiovascular disease (CVD) and associated mortality in individuals with type 2 diabetes, identifying and understanding predictors of CVD events and mortality could help inform clinical management in this high-risk group. Recent large-scale genetic studies may provide additional tools in this regard. RESEARCH DESIGN AND METHODS: Genetic risk scores (GRSs) were constructed in 1,175 self-identified European American (EA) individuals comprising the family-based Diabetes Heart Study based on 1) 13 single nucleotide polymorphisms (SNPs) and 2) 30 SNPs with previously documented associations with CVD in genome-wide association studies. Associations between each GRS and a self-reported history of CVD, coronary artery calcified plaque (CAC) determined by noncontrast computed tomography scan, all-cause mortality, and CVD mortality were examined using marginal models with generalized estimating equations and Cox proportional hazards models. RESULTS: The weighted 13-SNP GRS was associated with prior CVD (odds ratio [OR] 1.51 [95% CI 1.22–1.86]; P = 0.0002), CAC (β-coefficient [β] 0.22 [0.02–0.43]; P = 0.04) and CVD mortality (hazard ratio [HR] 1.35 [1.10–1.81]; P = 0.04) when adjusting for the other known CVD risk factors: age, sex, type 2 diabetes affection status, BMI, current smoking status, hypertension, and dyslipidemia. The weighted 30-SNP GRS was also associated with prior CVD (OR 1.33 [1.08–1.65]; P = 0.008), CAC (β 0.29 [0.08–0.50]; P = 0.006), all-cause mortality (HR 1.28 [1.05–1.56]; P = 0.01), and CVD mortality (HR 1.46 [1.08–1.96]; P = 0.01). CONCLUSIONS: These findings support the utility of two simple GRSs in examining genetic associations for adverse outcomes in EAs with type 2 diabetes.